Lithium-free negative electrode and preparation method thereof, and lithium metal battery comprising lithium-free negative electrode

By setting a metal layer and a graphene oxide layer in the lithium-free negative electrode of the lithium metal battery, combined with the alloying reaction of the nanometal layer, the problems of lithium dendrites growth and repeated formation of solid electrolytes are solved, and the Coulomb efficiency of lithium metal batteries is improved and capacity retention rate enhances the safety and stability of the battery.

CN119133364APending Publication Date: 2024-12-13JIANGSU ENPACK COMPOSITE CURRENT COLLECTORS CO LTD

Patent Information

Application Number
CN202411333035.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

During the lithium deposition and deliquification process of lithium metal batteries, uneven lithium deposition due to uneven negative electrode current collector and local uneven liquid mass transfer, which accelerates the growth of lithium dendrites, reduces battery utilization and safety, and at the same time, solid electrolytes The repeated formation of the battery curloss efficiency and capacity retention rate is limited.

Method used

A metal layer and a graphene oxide layer are arranged in the lithium-free negative electrode of a lithium metal battery. The metal layer is employed to suppress the growth of lithium dendrites by utilizing the plasma resonance effect of the metal layer and the high lithium-ion conductivity and stability of graphene oxide, and pass through the nanometal layer. LixY is generated with lithium ion alloying to form a stable SEI film, improving the rate performance and long-term stability of the battery.

Benefits of technology

Through uniform lithium deposition and stable formation of SEI film, the Coulomb efficiency and capacity retention of lithium metal batteries are improved, the safety and corrosion resistance of the battery are enhanced, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133364A_ABST
    Figure CN119133364A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-free negative electrode for a lithium metal battery, a preparation method of the lithium-free negative electrode and the lithium metal battery. The lithium-free negative electrode comprises a current collector, the metal layer is arranged on at least one side of the current collector, and the material of the metal layer is one or more of tin, magnesium, zinc, bismuth, lead, silver and aluminum; and the graphene oxide layer is arranged on one side, far away from the current collector, of the metal layer. According to the invention, the deposition uniformity of lithium at the negative electrode is improved to inhibit the growth of lithium dendrites, and the coulombic efficiency and the capacity retention ratio of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium metal battery production, and in particular to a lithium-free negative electrode and a preparation method thereof, and a lithium metal battery comprising the lithium-free negative electrode. Background Art

[0002] After dominating the consumer electronics market, lithium-ion batteries are rapidly expanding their applications in electric vehicles and power storage. However, with the large-scale application and development of new energy electric vehicles, higher requirements are placed on the lightweight and energy density of lithium batteries. In this context, lithium metal batteries (LMBs) have attracted people's attention. The lithium metal anode has become a hot topic of current research due to its ultra-high theoretical specific capacity (3860mAh / g) and the most negative electrode potential (-3.04V, equivalent to the standard hydrogen electrode). However, when you want to maximize the energy density of the battery, you usually need to carry ultra-thin lithium metal. Because metallic lithium has a high reactivity, it will react violently with oxygen and water in the air and explode, which leads to very strict requirements for the production environment of the battery. Based on this, lithium-free anode batteries have become a more ideal choice.

[0003] The lithium-free negative electrode does not use negative electrode active materials, but only uses negative electrode current collectors. During the first charging process, lithium plating is completed on the negative electrode, and then returns to the positive electrode during discharge to achieve a charge-discharge cycle. The lithium-free negative electrode not only greatly improves the energy density of the battery, but also avoids the inconvenience and safety hazards caused by the direct use of ultra-thin lithium metal in the actual production process.

[0004] At the same time, there are still some problems in the application of lithium-free negative electrodes. During the deposition and delithiation of lithium metal, uneven lithium deposition will occur due to the unevenness of the negative electrode current collector and the local uneven liquid phase mass transfer. Uneven lithium deposition will accelerate the growth of lithium dendrites, which will lead to the generation of dead lithium, causing the battery to expand in volume, reducing the utilization rate of lithium, and ultimately leading to a decrease in the electrochemical performance of the battery. Excessive growth of lithium dendrites will even increase safety hazards. In addition, the repeated formation of solid electrolytes (SEI) will accelerate the consumption of electrolytes and limit the lithium content, rapidly reducing the coulombic efficiency and capacity retention rate of the battery. Summary of the invention

[0005] In order to overcome the above-mentioned shortcomings, the purpose of the present invention is to provide a lithium-free negative electrode and a preparation method thereof, as well as a lithium metal battery comprising a lithium-free negative electrode, which not only improves the uniformity of lithium deposition on the negative electrode to inhibit the growth of lithium dendrites, but also improves the coulombic efficiency and capacity retention rate of the battery.

[0006] In order to achieve the above object, one of the technical solutions adopted by the present invention is: a lithium-free negative electrode for a lithium metal battery, comprising current collector; A metal layer, disposed on at least one side of the current collector, wherein the material of the metal layer is one or more of tin, magnesium, zinc, bismuth, lead, silver, and aluminum; The graphene oxide layer is disposed on a side of the metal layer away from the current collector.

[0007] The beneficial effects of the lithium-free negative electrode of the present invention are: By setting a metal layer on the current collector and utilizing the plasma resonance effect on the surface of the metal layer, the metal layer has a higher electronic conductivity, which can reduce the problem of local current density being too dense, thereby allowing lithium to be deposited evenly to inhibit the growth of lithium dendrites; the graphene oxide layer has a higher lithium ion conductivity, which can effectively promote the diffusion of lithium ions, and the oxygen-containing functional groups of graphene oxide can further promote the migration and distribution of lithium ions, improve the rate performance of lithium metal batteries, and allow lithium to be deposited evenly to inhibit the growth of lithium dendrites. The two-dimensional structure of graphene oxide can serve as a deposition template for lithium ions, guiding the uniform deposition of lithium ions and further reducing the formation of lithium dendrites. The graphene oxide layer can anchor the metal particles on the metal layer, making the lithium-philic sites more stable, while also avoiding the shedding of the lithium-philic sites during discharge, thereby improving the initial coulombic efficiency and capacity retention rate of the battery. In addition, using a graphene oxide layer as the outermost layer of the lithium-free negative electrode can utilize the stable electrochemical properties and mechanical strength of graphene oxide to suppress the problems of lithium precipitation and large changes in embedded volume, thereby improving the long-term stability of the battery. The stable electrochemical properties of graphene oxide can enhance the corrosion resistance of the lithium-free negative electrode.

[0008] Furthermore, the metal layer includes a nano-metal layer and a thickened metal layer which are sequentially arranged from close to the current collector to away from the current collector.

[0009] The nanometal particles in the nanometal layer can alloy with lithium ions to generate Li x Y (where Y is a metal), such as silver nanoparticles, can alloy with lithium ions to form Li x Ag, so during the lithiation process, the newly generated lithium can diffuse into the metal alloy to form an alloy phase, rather than being deposited on the metal surface to form metallic lithium. This alloying process avoids the deposition / stripping of lithium on the electrode surface and helps to form a stable SEI film. x The formation of Y alloy can achieve a lower nucleation potential, thereby regulating the deposition behavior of lithium and stabilizing the lithium-free negative electrode, giving lithium metal batteries better electrochemical performance and stability. In addition, the nanometal layer enables better contact between the lithium-free negative electrode and the electrolyte, promoting the transmission and distribution of lithium ions, thereby improving the battery's rate performance.

[0010] The smaller-sized nanometal particles in the nanometal layer can be better embedded in the surface of the current collector, so as to enhance the bonding force between the metal layer and the current collector; and setting a thickened metal layer on the surface of the nanometal layer can increase the overall thickness of the metal layer, so as to facilitate the uniformity of the metal layer on the surface of the current collector and ensure its electrical conductivity. At the same time, it can effectively prevent the nanometal layer from falling off and supply metal particles to the nanometal layer to ensure sufficient alloying.

[0011] Furthermore, the thickness of the nano metal layer is 8-12 nm, and the thickness of the thickened metal layer is 50-500 nm; and / or The nano-metal layer is prepared by in-situ photoreduction or laser reduction; the thickened metal layer is prepared by one or more of magnetron sputtering, vacuum evaporation, and water electroplating. In-situ photoreduction can make the prepared nano-metal layer more compact and more uniform in particle size. Plating metal on the surface of the nano-metal layer by magnetron sputtering, vacuum evaporation, and water electroplating can make metal particles deposit on the surface of nano-metal particles, so as to optimize the surface properties of the nano-metal particles and make them have better conductivity stability. Furthermore, the current collector is a composite copper foil, the composite copper foil comprises a polymer base film layer and the metal copper layer disposed on at least one side of the polymer base film layer, and the metal layer is disposed on the metal copper layer; The metal copper layer is prepared by one or more methods selected from magnetron sputtering, vacuum evaporation, and water electroplating, and the thickness of the metal copper layer is 0.5-10 μm; The polymer base film layer is made of at least one of polyamide, polyethylene terephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, aramid, polyphenylene dicarboxylate, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, polyparaphenylene terephthalamide, polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber, polycarbonate, cellulose and cellulose derivatives, starch and starch derivatives, protein and protein derivatives, polyvinyl alcohol and polyvinyl alcohol crosslinks, polyethylene glycol and polyethylene glycol crosslinks.

[0012] Furthermore, the graphene oxide layer is prepared by one or more methods selected from spin coating, blade coating, roller coating, ultrasonic spray coating, and slit coating, and the thickness of the graphene oxide layer is 10 to 500 nm.

[0013] Graphene oxide has a high lithium ion conductivity and can effectively promote the diffusion of lithium ions. During the discharge process, metal ions can easily enter the electrolyte from the alloy. The coating of the graphene oxide layer can anchor the metal ions, making the lithium-philic sites in the metal layer more stable. At the same time, it also avoids the shedding of lithium-philic sites during the charge and discharge process, thereby improving the stability of lithium-philic sites on the lithium-free negative electrode. The second technical solution adopted by the present invention is: a method for preparing a lithium-free negative electrode for a lithium metal battery, comprising the following steps: A metal layer is prepared on at least one side of the current collector, wherein the material of the metal layer is one or more of tin, magnesium, zinc, bismuth, lead, silver, and aluminum; Graphene oxide is coated on a surface of the metal layer away from the current collector.

[0014] The beneficial effects of the preparation method of the present invention are: By setting a metal layer on the current collector and utilizing the plasma resonance effect on the surface of the metal layer, the metal layer has a higher electronic conductivity, which can reduce the problem of local current density being too dense, thereby allowing lithium to be deposited evenly to inhibit the growth of lithium dendrites; the graphene oxide layer has a higher lithium ion conductivity, which can effectively promote the diffusion of lithium ions, and the oxygen-containing functional groups of graphene oxide can further promote the migration and distribution of lithium ions, improve the rate performance of lithium metal batteries, and allow lithium to be deposited evenly to inhibit the growth of lithium dendrites. The two-dimensional structure of graphene oxide can serve as a deposition template for lithium ions, guiding the uniform deposition of lithium ions and further reducing the formation of lithium dendrites. The graphene oxide layer can anchor the metal particles on the metal layer, making the lithium-philic sites more stable, while also avoiding the shedding of the lithium-philic sites during discharge, thereby improving the initial coulombic efficiency and capacity retention rate of the battery. In addition, using a graphene oxide layer as the outermost layer of the lithium-free negative electrode can utilize the stable electrochemical properties and mechanical strength of graphene oxide to suppress the problems of lithium precipitation and large changes in embedded volume, thereby improving the long-term stability of the battery. The stable electrochemical properties of graphene oxide can enhance the corrosion resistance of the lithium-free negative electrode.

[0015] Furthermore, it also includes one or more of the following characteristics: (1) The preparation method further comprises: performing a corona treatment on the surface of the current collector before preparing the metal layer; (2) The “coating graphene oxide on the surface of the metal layer away from the current collector” includes: coating graphene oxide on the surface of the metal layer away from the current collector by one or more of spin coating, scraper coating, roller coating, ultrasonic spray coating, and slit coating; (3) The current collector is a composite copper foil.

[0016] Further, the “preparing a metal layer on at least one side of the current collector” includes: Loading a nanometal layer on at least one side of the current collector by one or more of in-situ photoreduction or laser reduction; A thickened metal layer is prepared on the nano-metal layer by one or more methods including magnetron sputtering, vacuum evaporation or water electroplating.

[0017] Further, when the nanometal layer is loaded, the in-situ photoreduction includes: Place the current collector in a 5-100 mmol / L metal nitrate compound solution, soak for 5-10 minutes in a light-proof environment, and then wash with water; After irradiating with visible light for 5-10 minutes, washing with water and vacuum drying, a current collector loaded with a nano-metal layer is obtained.

[0018] The third technical solution adopted by the present invention is: a lithium metal battery, comprising any of the above-mentioned lithium-free negative electrodes. The lithium metal battery of the present invention can effectively inhibit the growth of lithium dendrites and improve the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic structural diagram of an embodiment of the present invention.

[0020] In the figure: 1-current collector; 11-polymer base film layer; 12-metal copper layer; 2-metal layer; 21-nanometal layer; 22-thickened metal layer; 3-graphene oxide layer. DETAILED DESCRIPTION The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0021] Example See attached Figure 1 As shown, a lithium-free negative electrode of the present invention includes a current collector 1, a metal layer 2, and a graphene oxide layer 3, wherein the metal layer 2 is disposed on at least one side of the current collector, and the graphene oxide layer 3 is disposed on a side of the metal layer away from the current collector. Specifically, the current collector 1 is a composite copper foil, and the composite copper foil includes a polymer base film layer 11 and a metal copper layer 12 disposed on at least one side of the composite copper foil.

[0022] First, the current collector 1 formed by the polymer base film layer 11 and the metal copper layer 12 can reduce the weight of the battery cell while ensuring the energy density of the battery cell. The current collector 1 has small burrs and a thermal circuit breaker effect, which can effectively prevent the thermal failure caused by lithium dendrites and greatly improve the life and safety of the battery. Secondly, by arranging a metal layer 2 on the current collector 1 and utilizing the plasma resonance effect on the surface of the metal layer 2, it has a higher electronic conductivity, thereby reducing the problem of excessive local current density, allowing lithium ions to be uniformly deposited to inhibit the growth of lithium dendrites. The metal particles have a lithium affinity, and the metal particles can be used to alloy with lithium ions to generate Li during the charging process. x Y (where Y is a metal) is used to promote the formation of a stable SEI film, achieve a lower nucleation potential and better electrochemical performance; finally, a graphene oxide layer 3 is arranged on the outermost layer, and the high lithium ion conductivity of graphene oxide is used to provide a transmission channel for lithium ions to promote the diffusion of lithium ions to the metal layer; and because metal ions can easily flow from Li x Y (where Y is a metal) alloy, at this time, the graphene oxide layer located outside the metal layer can anchor the detached metal ions, avoiding the loss of lithium-philic sites on the metal layer caused by the metal ions entering the electrolyte, ensuring the stability of the lithium-philic sites on the metal layer, which is conducive to improving the initial coulombic efficiency and capacity retention rate of the battery. In addition, using the graphene oxide layer as the outermost layer of the lithium-free negative electrode can utilize the stable electrochemical properties of graphene oxide to suppress the problem of lithium precipitation and the increase of embedded volume, and Li x Y (where Y is metal) alloy and graphene oxide have excellent electrochemical stability and can resist corrosion and side reactions.

[0023] In order to improve the energy density of the lithium-free negative electrode, a metal layer is usually provided on both sides of the current collector. The material of the metal layer is one or more of tin (Sn), magnesium (Mg), zinc (Zn), bismuth (Bi), lead (Pb), silver (Ag), and aluminum (Al). Exemplarily, the metal layer can be made of silver.

[0024] In some embodiments, in order to enhance the bonding stability between the metal layer 2 and the current collector 1, the metal layer 2 includes a nanometal layer 21 and a thickened metal layer 22 which are sequentially arranged from close to the current collector 1 to away from the current collector 1. The particle size of the nanometal particles in the nanometal layer 21 is 5 to 10 nm. The nanometal particles with smaller particle sizes in the nanometal layer 21 can be better embedded in the surface of the current collector, so as to enhance the bonding force between the metal layer 2 and the current collector 1, and the smaller particle size of the nanometal particles is more conducive to alloying reaction with lithium ions; and the thickened metal layer 22 is arranged on the surface of the nanometal layer 21 to increase the overall thickness of the metal layer 2, so as to facilitate the uniformity of the metal layer 2 on the surface of the current collector 1, ensure its electrical conductivity, and effectively prevent the nanometal layer 21 from falling off, and supply metal particles to the nanometal layer 21 to ensure the full alloying.

[0025] Furthermore, the thickness of the nano metal layer 21 is 8-12 nm, and the thickness of the thickened metal layer 22 is 50-500 nm. The nano metal layer 21 is prepared by in-situ photoreduction or laser reduction. The thickened metal layer 22 is prepared by at least one of magnetron sputtering, vacuum evaporation, and water electroplating.

[0026] In situ photoreduction is the process of reducing organic compounds to nanoparticles in water phase through the action of light. The nanoparticles prepared by in situ photoreduction have the characteristics of good density and uniform particle size.

[0027] The laser reduction method uses laser to reduce metal ions into nanoparticles under specific conditions. The nanoparticles prepared by the laser reduction method are affected by the laser irradiation method and energy density, and the morphology of the nanoparticles will be greatly different.

[0028] Magnetron sputtering is to fill a proper amount of argon gas under high vacuum, apply a DC voltage between the cathode (columnar target or flat target) and the anode (coating chamber wall), and generate a magnetron type abnormal glow discharge in the coating chamber to separate the argon gas. The argon ions are accelerated by the cathode and bombard the cathode target surface, sputtering the atoms on the target surface and depositing them on the substrate surface to form a thin film. By replacing targets of different materials and controlling different sputtering times, thin films of different materials and thicknesses can be obtained. The magnetron sputtering method has the characteristics of strong bonding between the coating layer and the substrate layer, and a dense and uniform coating layer.

[0029] Vacuum evaporation refers to a process in which a certain heating evaporation method is used to evaporate the coating material under vacuum conditions and gasify it, so that the particles fly to the surface of the substrate and condense into a film. Vacuum evaporation has the characteristics of simple film-forming process, high film purity and density, and unique film structure and performance.

[0030] Water electroplating is to use the electrochemical reaction between metal ions in the electrolyte and the metal matrix to reduce the metal ions into a metal coating. Water electroplating has the characteristics of simple operation, low cost, uniform coating and high precision.

[0031] It should be noted that the thickened metal layer prepared by magnetron sputtering, vacuum evaporation and water electroplating will not form a dense structure, and therefore will not affect the alloying reaction between the nano-metal particles and lithium ions.

[0032] In some embodiments, the material of the polymer base film layer 11 is at least one of polyamide, polyterephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, aramid, polyphenylene diamine, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, polyparaphenylene terephthalamide, polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber, polycarbonate, cellulose and cellulose derivatives, starch and starch derivatives, proteins and protein derivatives, polyvinyl alcohol and polyvinyl alcohol crosslinks, polyethylene glycol and polyethylene glycol crosslinks.

[0033] In some embodiments, the metal copper layer 12 is prepared by at least one of magnetron sputtering, vacuum evaporation, and water electroplating, and the thickness of the metal copper layer is 0.5-10 μm. In some embodiments, the graphene oxide layer 3 is prepared by at least one of spin coating, blade coating, roller coating, ultrasonic spray coating, and slit coating, and the thickness of the graphene oxide layer is 10-500 nm.

[0034] The present invention also provides a preparation method for a lithium metal battery, comprising: preparing a metal layer on at least one side of a current collector, wherein the material of the metal layer is one or more of tin (Sn), magnesium (Mg), zinc (Zn), bismuth (Bi), lead (Pb), silver (Ag), and aluminum (Al); and coating graphene oxide on the surface of the metal layer away from the current collector.

[0035] Furthermore, the preparation includes one or more of the following features: (1) the preparation method further includes: performing corona treatment on the surface of the current collector before preparing the metal layer; (2) the "coating graphene oxide on the surface of the metal layer away from the current collector" includes: coating graphene oxide on the surface of the metal layer away from the current collector by one or more methods selected from spin coating, scraping, roller coating, ultrasonic spraying, and slit coating; (3) the current collector is a composite copper foil.

[0036] Preparing a metal layer on at least one side of the current collector comprises: loading a nano-metal layer on at least one side of the current collector by one or more of in-situ photoreduction or laser reduction; A thickened metal layer is prepared on the nano-metal layer by one or more methods including magnetron sputtering, vacuum evaporation or water electroplating.

[0037] When the nanometal layer is loaded by in-situ photoreduction, the current collector is placed in a 5-100 mmol / L metal nitrate solution (such as tin nitrate, magnesium nitrate, zinc nitrate, bismuth nitrate, lead nitrate, silver nitrate, aluminum nitrate and other solutions), immersed in a light-proof environment for 5-10 min and then washed with water; after irradiating with visible light for 5-10 min, washed with water again, and vacuum dried to obtain the current collector loaded with the nanometal layer.

[0038] When the thickened metal layer is prepared by magnetron sputtering, the current collector loaded with the nanometal layer is placed in a vacuum chamber, and the vacuum chamber is evacuated until the vacuum degree in the chamber is greater than 4*10 -4 Pa; introduce argon gas at a flow rate of 15sccm into the chamber, and turn on the ion source for 5 minutes to clean the current collector loaded with the nanometal layer; after the cleaning is completed, turn off the ion source, turn on the metal target power supply and argon gas flow controller at the same time, and introduce argon gas at a flow rate of 40sccm for glow discharge, and argon ions bombard the metal target material so that the metal target material is plated on the nanometal layer; when the coating thickness reaches the requirement, turn off the metal target power supply and argon gas flow controller, and cut off the argon gas inlet.

[0039] When vacuum evaporation is used to prepare a thickened metal layer, a metal evaporation source and a current collector loaded with a nanometal layer are placed in an evaporation device, and the evaporation source is directed toward the current collector loaded with the nanometal layer. The evaporation source is heated by a laser so that the evaporation source evaporates metal particles toward the current collector loaded with the nanometal layer, and the metal particles are then deposited on the surface of the nanometal layer.

[0040] When the thickened metal layer is prepared by water electroplating, a current collector loaded with a nanometal layer is placed in an electrolytic cell and serves as a cathode; an electrolyte containing metal ions is then poured into the electrolytic cell, and a metal plate is placed in the electrolytic cell as an anode. By applying an external current, the metal ions are reduced to a metal coating in the electrolyte and deposited on the nanometal layer of the current collector serving as the cathode.

[0041] Example 1 A composite copper foil with a thickness of 6.5 μm was selected as the current collector, and the composite copper foil was subjected to corona activation treatment by a corona machine to enhance its surface tension. The pretreated composite copper foil was placed in a 15mmol / L tin nitrate solution, soaked for 5-10min in a light-proof environment, filtered and washed three times, transferred to ultrapure water, irradiated with a 10W xenon lamp for 4h, washed three times with ultrapure water, and dried at 60℃ in vacuum for 3h to obtain a current collector loaded with an 8nm thick nano-tin layer; The current collector loaded with the 8 nm thick nano-tin layer is subjected to water electroplating by using a 15CHI 660E electrochemical workstation to form an electroplated tin layer with a thickness of 300 nm on the surface of the 8 nm thick nano-tin layer; A 300 nm graphene oxide layer was coated on the surface of the electroplated tin layer by spin coating to obtain a negative electrode sample.

[0042] Example 2 A composite copper foil with a thickness of 6.5 μm was selected as the current collector, and the composite copper foil was subjected to corona activation treatment by a corona machine to enhance its surface tension. The pretreated composite copper foil was immersed in a 25mmol / L silver nitrate solution, immersed in a light-proof environment for 5-10 minutes, filtered and washed three times, transferred to ultrapure water, irradiated with a 10W xenon lamp for 4 hours, washed three times with ultrapure water, and placed at 60°C for vacuum drying for 3 hours to obtain a current collector loaded with a 10nm thick nanosilver layer; The current collector loaded with the 10 nm thick nanosilver layer was electroplated with water using a 15CHI 660E electrochemical workstation to form a 400 nm electroplated silver layer on the surface of the 10 nm thick nanosilver layer; A 300 nm graphene oxide layer was coated on the surface of the electroplated silver layer by spin coating to obtain a negative electrode sample.

[0043] Example 3 A composite copper foil with a thickness of 6.5 μm was selected as the current collector, and the composite copper foil was subjected to corona activation treatment by a corona machine to enhance its surface tension. The pretreated composite copper foil was immersed in a 20mmol / L magnesium nitrate solution, immersed for 5-10min in a light-proof environment, filtered and washed 3 times, transferred to ultrapure water, irradiated with a 10W xenon lamp for 4h, washed 3 times with ultrapure water, and dried at 60℃ in vacuum for 3h to obtain a current collector loaded with a 10nm thick nano-magnesium layer; The current collector loaded with the 10 nm thick nano-magnesium layer is electroplated with water using a 15CHI 660E electrochemical workstation to form a 400 nm electroplated magnesium layer on the surface of the 10 nm thick nano-magnesium layer; A 300 nm graphene oxide layer was coated on the surface of the electroplated magnesium layer by spin coating to obtain a negative electrode sample.

[0044] Comparative Example 1 A metal copper foil with a thickness of 6.5 μm was selected as the current collector, and the metal copper foil was corona activated by a corona machine to enhance its surface tension; a 300 nm graphene oxide layer was coated on the surface of the metal copper foil by spin coating to obtain a negative electrode sample.

[0045] Comparative Example 2 A metal copper foil with a thickness of 6.5 μm was selected as the current collector, and the metal copper foil was subjected to corona activation treatment by a corona machine to enhance its surface tension; The pretreated metal copper foil was immersed in a 15mmol / L silver nitrate solution, immersed for 5-10min in a light-proof environment, filtered and washed 3 times, transferred to ultrapure water, irradiated with a 10W xenon lamp for 4h, washed 3 times with ultrapure water, and dried in a vacuum at 60°C for 3h to obtain a current collector loaded with an 8nm thick nanosilver layer; a 15CHI660E electrochemical workstation was used to perform water electroplating on the current collector loaded with an 8nm thick nanosilver layer to form a 300nm electroplated silver layer on the surface of the 8nm thick nanosilver layer to obtain a negative electrode sample.

[0046] Comparative Example 3 The composite copper foil with a thickness of 6.5 μm was directly used as the negative electrode sample.

[0047] Experimental testing The negative electrode samples in Examples 1-3 and Comparative Examples 1-3 were respectively cut into discs with a diameter of 12 mm by a punching machine for use; the discs punched out in Examples 1-3 and Comparative Examples were respectively used as negative electrode materials for lithium metal batteries, lithium iron phosphate was used as the positive electrode material for lithium metal batteries, 1 mol / L LiPF6 (the solvent composition was EC:DMC:EMC=1:1:1) was used as the electrolyte, and a polypropylene microporous film was used as the diaphragm, and the battery was assembled in a glove box filled with argon (H2O <1ppm, O2 <1ppm).

[0048] The assembled battery was charged and discharged at constant current to test the initial coulombic efficiency and capacity retention rate. The test results are shown in Table 1. The constant current charge and discharge voltage range is 0.01~1V, and the charge and discharge current is 0.1C.

[0049] Table 1 Test results of Examples 1-3 and Comparative Examples

[0050] From Table 1 we can see that: Compared with Comparative Examples 1-3, the initial coulombic efficiency of Examples 1-3 using the lithium-free negative electrode of the present invention is higher. And after 100 cycles of the lithium metal battery, Examples 1-3 still maintain a high capacity retention rate, while the capacity retention rate of Comparative Examples 1-3 drops rapidly after 50 cycles. The reason is that the metal layer in the present invention can modify the surface of the current collector so that lithium is more evenly deposited on the negative electrode during the charging process, thereby inhibiting the growth of lithium dendrites; at the same time, due to the alloying reaction between metal particles and lithium ions, the stable formation of the SEI film can be promoted, avoiding the decrease in the coulombic efficiency and capacity retention rate of the battery caused by the repeated formation of the SEI film. And the graphene oxide layer can anchor the metal particles, making the lithium-philic sites of the negative electrode more stable, so as to further improve the initial coulombic efficiency and capacity retention rate of the battery.

[0051] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium-free negative electrode for a lithium metal battery, characterized in that: include current collector; A metal layer, disposed on at least one side of the current collector, wherein the material of the metal layer is one or more of tin, magnesium, zinc, bismuth, lead, silver, and aluminum; The graphene oxide layer is disposed on a side of the metal layer away from the current collector.

2. The lithium-free negative electrode for a lithium metal battery according to claim 1, characterized in that: The metal layer comprises a nano metal layer and a thickened metal layer which are sequentially arranged from close to the current collector to away from the current collector.

3. The lithium-free negative electrode for a lithium metal battery according to claim 2, characterized in that: The thickness of the nano metal layer is 8-12 nm, and the thickness of the thickened metal layer is 50-500 nm; and / or The nano-metal layer is prepared by in-situ photoreduction or laser reduction; the thickened metal layer is prepared by one or more of magnetron sputtering, vacuum evaporation, and water electroplating.

4. The lithium-free negative electrode for a lithium metal battery according to claim 1, characterized in that: The current collector is a composite copper foil, which includes a polymer base film layer and a metal copper layer disposed on at least one side of the polymer base film layer, and the metal layer is disposed on the metal copper layer; The metal copper layer is prepared by one or more methods selected from magnetron sputtering, vacuum evaporation, and water electroplating, and the thickness of the metal copper layer is 0.5-10 μm; The polymer base film layer is made of at least one of polyamide, polyethylene terephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, aramid, polyphenylene dicarboxylate, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, polyparaphenylene terephthalamide, polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber, polycarbonate, cellulose and cellulose derivatives, starch and starch derivatives, protein and protein derivatives, polyvinyl alcohol and polyvinyl alcohol crosslinks, polyethylene glycol and polyethylene glycol crosslinks.

5. The lithium-free negative electrode for a lithium metal battery according to claim 1, characterized in that: The graphene oxide layer is prepared by one or more methods of spin coating, scraper coating, roller coating, ultrasonic spray coating, and slit coating, and the thickness of the graphene oxide layer is 10-500 nm.

6. A method for preparing a lithium-free negative electrode for a lithium metal battery, characterized in that: The steps include: A metal layer is prepared on at least one side of the current collector, wherein the material of the metal layer is one or more of tin, magnesium, zinc, bismuth, lead, silver, and aluminum; Graphene oxide is coated on a surface of the metal layer away from the current collector.

7. The preparation method according to claim 6, characterized in that: Also includes one or more of the following characteristics: (1) The preparation method further comprises: performing a corona treatment on the surface of the current collector before preparing the metal layer; (2) The “coating graphene oxide on the surface of the metal layer away from the current collector” includes: coating graphene oxide on the surface of the metal layer away from the current collector by one or more of spin coating, scraper coating, roller coating, ultrasonic spray coating, and slit coating; (3) The current collector is a composite copper foil.

8. The preparation method according to claim 6 or 7, characterized in that: The “preparing a metal layer on at least one side of the current collector” includes: Loading a nanometal layer on at least one side of the current collector by one or more of in-situ photoreduction or laser reduction; A thickened metal layer is prepared on the nano-metal layer by one or more methods including magnetron sputtering, vacuum evaporation or water electroplating.

9. The preparation method according to claim 8, characterized in that: When the nanometal layer is loaded, the in-situ photoreduction comprises: Place the current collector in a 5-100 mmol / L metal nitrate compound solution, soak for 5-10 min in a light-proof environment, and then wash with water; After irradiating with visible light for 5-10 minutes, washing with water and vacuum drying, a current collector loaded with a nano-metal layer is obtained.

10. A lithium metal battery, characterized in that: The invention comprises the lithium-free negative electrode as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Negative current collector and preparation method and application thereof

    CN115911401A

  • Graphene oxide assisted seed crystal stabilized composite negative electrode and preparation method and application thereof

    CN115986059A

  • KR20220054074A

Cited By

  • In-situ generated lithium-free negative electrode with gradient lithiated three-dimensional structure and preparation method of lithium-free negative electrode

    CN120914196A

  • Negative plate of solid-state battery and solid-state battery

    CN121416421A